Rice husk and husk biochar soil amendments store soil carbon while water management controls dissolved organic matter chemistry in well-weathered soil. (1st August 2023) - Linam, Franklin; Limmer, Matt A.; Ebling, Alina M.; Seyfferth, Angelia L.
Abstract: Rice agriculture feeds over half the world's population, and paddy soils impact the carbon cycle through soil organic carbon (SOC) preservation and production of carbon dioxide (CO2 ) and methane (CH4 ), which are greenhouse gases (GHG). Rice husk is a nutrient-rich, underutilized byproduct of rice milling that is sometimes pyrolyzed or combusted. It is unresolved how the incorporation of these residues affects C dynamics in paddy soil. In this study, we sought to determine how untreated (Husk), low-temperature pyrolyzed (Biochar), and combusted (CharSil) husk amendments affect SOC levels, GHG emissions, and dissolved organic matter (DOM) chemistry. We amended Ultisol paddy mesocosms and collected SOC and GHG data for three years of rice grown under alternate wetting and drying (AWD) conditions. We also performed a greenhouse pot study that included water management treatments of nonflooded, AWD, and flooded. Husk, Biochar, and CharSil amendments and flooding generally increased SOC storage and CH4 emissions, while nonflooded conditions increased N2 O emissions and nonflooded and CharSil treatments increased CO2 emissions. All amendments stored ∼0.15 kg C m −2 y −1 more SOC than CH4 emissions (as CO2 equivalents), but the combustion of husk to produce CharSil resulted in the net release of CO2 which negates any SOC storage. UV–visible absorption/fluorescence spectroscopy from the pot study suggests that nonflooded treatment decreased DOM aromaticity and molecular size. Our data show that flooding and amendment of Husk and Biochar maximized C storage in the highly weathered rice paddy soil under study despite Husk increasing CH4 emissions. Water management affected dissolved organic matter chemistry more strongly than amendments, but this requires further investigation. Return of rice husk that is untreated or pyrolyzed at low temperature shows promise to close nutrient loops and preserve SOC in rice paddy soils. Graphical abstract: Image 1 Highlights: Rice husk and husk biochar amendments were assessed for effects on soil C. Husk amendments store a net 0.15 kg C m −2 y −1 despite increased CH4 emissions. High-temperature combustion of rice husk emits more C as CO2 than it stores as SOC. Water management affects DOM chemistry more than husk amendments. Flooding paddy soil produces DOM that is more aromatic and larger.